The worth of education - Abd Razak, Dzulkifli (2010)
IT is not difficult to detect a celebratory mood in Doha, Qatar these days. The joy of winning the bid to host the World Cup in 2022 — making Qatar the first Arab nation to do so — is still very much in the air.